REPRESENTASI PEREMPUAN DALAM NOVEL TERUSIR KARYA BUYA HAMKA: KAJIAN FEMINISME EKSISTENSIAL SERTA IMPLIKASINYA DALAM PEMBELAJAN SASTRA DI SMA - Martin, Megasari; Rifalda, Azri; Delni, Delni (Inovasi Pendidikan, 2025)
This study examines the representation of women in Terusir, a novel by Buya Hamka, through the lens of existentialist feminism. The main character, Mariah, is portrayed as a woman who experiences gender injustice within a patriarchal society. She faces various forms of marginalization, including abandonment by her husband, social stigma, workplace discrimination, physical and psychological violence, and coercion into sex work. Despite these adversities, Mariah is depicted as a strong, independent, courageous, and resilient figure. This research employs a descriptive qualitative approach. Data collection was carried out through a literature review. This research employs a qualitative descriptive method, using literature review and close reading techniques. The findings reveal that the novel not only reflects the social conditions of women during its time but also offers a critique of gender inequality. Furthermore, the novel holds potential as an instructional resource for high school literature education, particularly in analyzing social values and extrinsic elements of literary works. Through the use of Terusir in the classroom, students are expected to develop critical awareness of gender issues and gain a deeper understanding of women's roles in both cultural and literary contexts. Bedakan  3 paragraf (resume latar belakang dan tujuan